Why rights are not optimisation requirements. (3rd July 2019) - Zanghellini, Aleardo
ABSTRACT: In this article I pursue the implications of the statement that constitutional rights are – as Alexy's principles theory argues – optimisation requirements, and show that they are not. I argue that, applied to moral rights, optimisation obfuscates their nature, their relationship to human well-being, and the work they do in practical thought. As to constitutional rights, the fact that they belong in an institutional framework suggests some reasons for treating them like optimisation requirements in circumscribed cases. But these reasons are far from conclusive; and treating rights like optimisation requirements in other scenarios (such as cases of structural discretion) indicates that optimisation, as defined in the principles theory, does not assist us in thinking well about the structure of constitutional rights. Constitutional rights demand compliance with whatever the interests on which they are based demand – whether or not what they demand is antecedently clear – not with some purported optimisation requirement.